Financial accounting made simple - Igben, Robert Orighotsuwa (Lagos : Dynamics Book Home, 2022)
This 6th edition is part of the never-ending efforts to update this acclaimed book to ensure its continued relevance. It examines financial accounting processes according to IFRS Compliant.
Includes index
usc 23/11/2022
Loans
Keywords: Accounting; Accounting--Moral and ethical aspects; Nigeria